The Influence of Islamic Civilization on The World of Education - Siregar, Hotnida; Matondang, Nur Azizah; Nasution, Abdusima (International Journal of Curriculum Development, Teaching and Learning Innovation, 2025)
This study aims to examine the influence of Islamic civilization on the development of education from the classical period to the heyday of the Umayyad and Abbasid dynasties. The study was conducted through library research by analyzing various relevant literature related to the history of Islamic civilization, education systems, and the contributions of Muslim scientists. The results of the study show that Islamic civilization played an important role in shaping the foundations of comprehensive education, including strengthening philosophical foundations, integrating religious and rational sciences, and developing the ethics and character of students. During the Umayyad Dynasty, educational institutions developed through kuttab, mosques, literary assemblies, palace education, and bādiah. Meanwhile, during the Abbasid Dynasty, madrasas emerged as formal educational institutions, as well as Bait al-Hikmah as a center for libraries, observatories, research, and translation. In addition, Muslim scientists made significant contributions to various fields of science such as medicine, astronomy, philosophy, Islamic law, and mathematics, which became the basis for the development of world science. In conclusion, Islamic civilization has had a significant influence on the world of education through educational institutions, learning systems, and scientific works that have contributed to the advancement of global knowledge